RELIGION, A COUNTER CULTURE - Nandhikkara, Jose (Journal of Dharma, 2009)
Homo sapiens is homo religious; rational human beings are also capable of believing, which is as important as reasoning for human survival, growth and development. Though we seek the truth, we live also by belief. There are in our lives many more truths than are acquired by way of scientific personal verification. Answers to the fundamental questions like Who am I? Where have I come from and where am I going? Why is there evil? and What is there after this life? are often related with belief in God: "To believe in a God means to understand the question about the meaning of life. To believe in a God means to see that the facts of the world are not the end of the matter. To believe in God means to see that life has a meaning.